If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+5+7=8(x-1)-3
We move all terms to the left:
2x+5+7-(8(x-1)-3)=0
We add all the numbers together, and all the variables
2x-(8(x-1)-3)+12=0
We calculate terms in parentheses: -(8(x-1)-3), so:We get rid of parentheses
8(x-1)-3
We multiply parentheses
8x-8-3
We add all the numbers together, and all the variables
8x-11
Back to the equation:
-(8x-11)
2x-8x+11+12=0
We add all the numbers together, and all the variables
-6x+23=0
We move all terms containing x to the left, all other terms to the right
-6x=-23
x=-23/-6
x=3+5/6
| -⅚(-12h-18)=935 | | 2m-19=22+2m | | 13y-17+172=180 | | 2m-19=2+2m | | 2(2x-5)=2-2x | | 2x(x-3.5)=4 | | 9n=3(10-2n) | | -1.5s+19.25=-8.7-18.91 | | -6x+2=4(6-x) | | (√34)x=81 | | 4.1g+5=2.1+17 | | -1.5s+19.25=-8.7s-18.91 | | 5x-17+4x+17=180 | | 3x-10=4x5 | | -5x-9x-170=138 | | -5x+14=-10x-16 | | -38=84-30x | | 5x+17+4x+17+90=180 | | 5/3x-1/3=13+42/18x | | -9.65+19.4y=19.9y | | -16+4x=6x-10 | | 9(n+6)=-5n-2 | | V(-2)=12-2x-5 | | 1350/6=k | | 5x+17+4x+17=180 | | -x/3+2=10 | | 2(✔–6y+29)–4y=–6 | | -5-10t=20t-5-4t | | 1.5w+12=26 | | 3x+19+4x−2=180 | | 6(18−x)=54 | | 5y+70=55 |